Community-based recruitment and exome sequencing indicates high diagnostic yield in adults with intellectual disability. - Sabo, Aniko; Murdock, David; Dugan, Shannon; Meng, Qingchang; Gingras, Marie-Claude; Hu, Jianhong; Muzny, Donna; Gibbs, Richard (Mol Genet Genomic Med, 2020)
BACKGROUND: Establishing a genetic diagnosis for individuals with intellectual disability (ID) benefits patients and their families as it may inform the prognosis, lead to appropriate therapy, and facilitate access to medical and supportive services. Exome sequencing has been successfully applied in a diagnostic setting, but most clinical exome referrals are pediatric patients, with many adults with ID lacking a comprehensive genetic evaluation. METHODS: Our unique recruitment strategy involved partnering with service and education providers for individuals with ID. We performed exome sequencing and analysis, and clinical variant interpretation for each recruited family. RESULTS: All five families enrolled in the study opted-in for the return of genetic results. In three out of five families exome sequencing analysis identified pathogenic or likely pathogenic variants in KANSL1, TUSC3, and MED13L genes. Families discussed the results and any potential medical follow-up in an appointment with a board certified clinical geneticist. CONCLUSION: Our study suggests high yield of exome sequencing as a diagnostic tool in adult patients with ID who have not undergone comprehensive sequencing-based genetic testing. Research studies including an option of return of results through a genetic clinic could help minimize the disparity in exome diagnostic testing between pediatric and adult patients with ID.
Keywords: Adult; Female; Genetic Testing; Humans; Independent Living; Intellectual Disability; Male; Mediator Complex; Membrane Proteins; Nuclear Proteins; Patient Selection; Sensitivity and Specificity; Tumor Suppressor Proteins; Whole Exome Sequencing

"Matching" consent to purpose: The example of the Matchmaker Exchange. - Dyke, Stephanie O M; Knoppers, Bartha M; Hamosh, Ada; Firth, Helen V; Hurles, Matthew; Brudno, Michael; Boycott, Kym M; Philippakis, Anthony A; Rehm, Heidi L (Hum Mutat, 2017)
The Matchmaker Exchange (MME) connects rare disease clinicians and researchers to facilitate the sharing of data from undiagnosed patients for the purpose of novel gene discovery. Such sharing raises the odds that two or more similar patients with candidate genes in common may be found, thereby allowing their condition to be more readily studied and understood. Consent considerations for data sharing in MME included both the ethical and legal differences between clinical and research settings and the level of privacy risk involved in sharing varying amounts of rare disease patient data to enable patient matches. In this commentary, we discuss these consent considerations and the resulting MME Consent Policy as they may be relevant to other international data sharing initiatives.
Keywords: Databases, Genetic; Genetic Association Studies; Genetic Diseases, Inborn; Genomics; Humans; Information Dissemination; Patient Selection; Physicians; Rare Diseases; Research Personnel; Translational Medical Research